AN EVALUATION OF THE YOUTUBE CHANNEL CONTENTS OF NGOS CARRYING OUT NON-FORMAL RELIGIOUS EDUCATION ACTIVITIES IN THE CONTEXT OF CIVIL RELIGIOUS EDUCATION - Tüken, Yunus; Karateke, Tuncay (My University, 2023)
With the introduction of the internet into our lives since the end of the 20th century, a rapid digitalization era has been entered in communication. This rapid digitalization has led to changes and innovations in all areas of life. Many states have taken their share from these changes and innovations. This is also the case for Turkey. This innovation and change mobility has not been limited to states only. There have also been great changes and movements in non-governmental organizations that act independently from states/governments. The public sphere in which people interact with each other and with states in order to act on behalf of their interests is expressed as civil society. Non-governmental organizations, on the other hand, are defined as organizations that act in line with the interests of societies, that individuals participate on a voluntary basis, that are independent of political power, and that are established in accordance with laws that include different groups. One of the most important features of non-profit, voluntary non-governmental organizations that cooperate with the state when necessary but are not bureaucratic is that they act for the solution of social problems. Education is one of the fields in which nongovernmental organizations that provide social support take an active role in order to find solutions to the problems of societies and to contribute directly to the development of societies. 5% of associations and 32% of foundations in Turkey operate in the field of education. These organizations continue their educational activities through various tools such as courses and media, and through various institutions. Educational activities carried out by non-governmental organizations are defined as non-educational activities. Religion is one of the fields that non-governmental organizations that carry out both supportive activities in formal education and directly non-formal education activities take as the subject of education. This religious education, which especially comes to the fore in the dimension of non-formal education, can be defined as civil religious education. Along with the developing technology and the changing world, there have been changes in the institutions where nonformal education is made. Institutions, where non-formal religious education took place, were not limited to institutions such as mosques and Qur’an courses. Media and social media, which are today’s communication and interaction networks, have also been added to the areas where non-formal religious education activities take place. Along with digitalization, digital channels such as Youtube, Facebook and Twitter were established and religious education activities were started to be carried out by both individuals and organizations in these channels. Along with digitalization, one of the institutions that carry out religious education activities in these channels is non-governmental organizations. Religious education activities are carried out by some non-governmental organizations on many platforms, especially Youtube. Youtube stands out as a platform that is used by 94.5% of social media users in our country and has users from all age groups. Religious education activities are also carried out by non-governmental organizations through the contents published on the Youtube platform. It is also important by which organizations this civil religious education, whose activities are evaluated within the scope of non-formal religious education activities on Youtube. In this research, it is aimed to examine the religious education activities carried out by non-governmental organizations on Youtube. In this direction, the non-governmental organizations channels with the most subscribers on Youtube and the examination of the most watched content on these channels constitute the subject of this research. In this study, which was car ried out in the case study design, one of the qualitative research designs, data were collected with the criterion sampling technique, which is defined as examining the cases that meet the predetermined criteria, one of the purposeful sampling methods. The collected data was subjected to content analysis. As a result of the research, it has been seen that the most followed Youtube channels of non-governmental organizations in Turkey are Sözler Köşkü, Hayalhanem, Fussilet Quran Center, Social Texture Foundation and Siyer TV. In the study, the data obtained from the popular contents of these channels were coded in accordance with the content analysis. In addition, it has been determined that the themes covered in the popular contents of these channels are Qiraa, Family, Faith, Fiqh, Worship, Prophets and Values and evaluations have been made on the themes.
Keywords: Youtube; Social Media; Religious Education; Non-Governmental Organizations; Non-Formal Education